Risk Management in Public Organizations - Peter-Bombik , Katarzyna (Management and Administration Journal, 2017)
Uncertainty is a constant element of reality. It causes that the action strategies as well as the prediction of specific events and phenomena often fail. In the activities of organizations all sorts of risks appear which can affect their performance in different ways in the present and the future. Risk management (understood as its identification, estimation, and also the determination of appropriate responses) becomes an integral part of the activity. This also refers to public organizations